Brand Logo Design Training for The Small-Medium Batik Enterprise in Kalitengah Village Cirebon West Java Indonesia - Feny Puspitasari; mila karmila; Katiah Katiah; Marlina Marlina; Asri Andarini Nurlita (ABMAS, 2024)
This paper is a result based on the community service activity in Kalitengah village, Tengahtani sub-disctrict, Cirebon, West Java, Indonesia. The aim is to support the batik enterprises towards a more independent and better but still profit-oriented even in a pandemic situation. They have many problems in the sale and marketing system, and they don't have a brand logo yet.  This paper focused on brand logo design training because the small-medium batik enterprises need a brand logo. The brand logo will help them for a differentiator, identity, and develop an online promotion for their business and earn more profit. The methods used participatory action research (PAR). The steps are 1) field survey; 2) workshops; 3) mentoring; 4) Empowering; 5) Evaluation and follow up. The study involved 2 (two)  small-medium batik enterprises;  Selva Batik and Batik Habibah. The result is the logo of Selva batik's more contemporary, modern impressions whereas the logo of Batik Habibah has traditional and decisive impressions. Both logos have represented their enterprises as a part of Batik Pesisir Cirebon and had reached the stage from unbranded to brand as a reference, brand as personality, and brand as an icon.